The humorous aspect of Stanisław Apolinary Zambrzycki’s poems - Karpiński, Ignacy (Laughter, humour, satire, 2024)
The subject of the article is humorous, satirical and ironic aspects of poems written by Stanisław Apolinary Zambrzycki who was a polish landowner living in 1824–1908 in his Wiazynka estate situated in Minsk governorate, in Russian Empire. Poems were being created from 60s in XIX to the death of poet in 1908. In work author presented the history of the poet’s family, his social and material position, personality and environment in which he existed. Cross-sectionally were displayed pieces of poems describing important events ocurring in poet’s life but also everyday life affairs. Poems refer to author’s family, neighbours, friends and whole groups of the society. Poetry presents personality, mentality, the way of thinking and sense of humor of Polish, middle class, provincional landowner.